Comprehensive Analysis of TGF β & β – Catenin Components in Various Human Cancer Tissues - Sameer Daraghmeh, Jamila; Mustafa Mansour, Bayan; Yousef Kmail, Asmaa; Ghalib Daraghmeh, Iqab (Journal of Applied Biotechnology, 2021)
Studies over the last years revealed significant insights into the β-Catenin & TGF β signal transduction pathways and that such pathways are abnormal activated in abundant cancer types. According to the straight forward effect of these pathways in various tumor types, both pathways are currently considered targets for innovative cancer therapies. This view study emphasizes 13 proteins that are implicated in these two pathways. As there has been widespread research into the proteins that involved in these pathways, we have utilized data existing in the Human Protein Atlas database in this paper to examine the expression of 53 crucial proteins that are recognized to be involved in the activation of these pathways in a distinct group of 45 cancer types. Our findings revealed notably that the proteins (SKIL, SHC, ERK1/2, RAS, PI3K (PIK3CA), SMAD8, ACVR2A/1B SNON, AKT, and SMAD3, from TGF β and (RNF43, SNAIL1 and DVl) for β catenin show high expression in most caner tissues. Our results strongly suggest that these proteins might have the ability to act as potential objects for remedies and provide perception into the molecular basis of cancer.